Genetics of fertility restoration of the A5 cytoplasm in pearl millet (Pennisetum glaucum) - R, THRIBHUVAN; SINGH, S P; S, MUKESH SANKAR; MALLIK, M; SINGHAL, TRIPTI; YADAV, PRACHI; SINGH, NIRUPMA; SATYAVATHI, C TARA (The Indian Journal of Agricultural Sciences, 2020)
For the efficient hybrid seed production, several cytoplasmic-nuclear male sterility (CMS) systems were identified in pearl millet (Pennisetum glaucum ( L) R. Br). However, most of the hybrids developed in pearl millet are based on A1 cytoplasm due to availability of high frequency of restorers in the natural population. This dependence on a single cytoplasm makes any hybrid seed industry vulnerable to disease and insect pest epidemics. A5 can be a good alternative to A1 since it is the most stable cytoplasm available. But due to very low frequency (~2%) of restorers available in germplasm, utilization of A5 cytoplasm in hybrid development had been almost negligible. Restorer breeding efficiency of this CMS system can be significantly increased by understanding the inheritance of fertility restoration by Rf-gene for A5 cytoplasm, which is poorly studied so far and only one publication is available. Present investigation aims to understand the genetics associated with fertility restoration of the A5 system of CMS in pearl millet using pollen fertility and seed set percent as a criterion in determining the fertile and sterile plants. Three diverse cytoplasmic-nuclear male-sterile A-lines belonging to the A5 cytoplasm (ICMA502555, ICMA507999 and ICMA512222) were crossed with two restorer lines (A5RT-17/8 and A5 RT-17/26) to produce 6 F1s and their respective F2s and backcrosses. These were evaluated for male sterility (S) and fertility (F) at ICAR-IARI, New Delhi during kharif 2019 and segregation ratio was established in all the generations using χ2 test. The segregation pattern of malesterile (S) and male fertile (F) plants observed in F2 and BC1 indicated dominant single-gene control of male fertility restoration with ICMA502555 and ICMA507999. However, segregation pattern with male-sterile line ICMA512222 had a good fit to 15F:1S ratio indicating two gene control with duplicate interaction. The deviations from the expected ratio with ICMA512222 cross may be due to influence of modifiers. Association between pollen fertility and seed set percent was significant and positive.